2015
DOI: 10.2463/mrms.2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Size-selective Permeability of the Synovial Membrane of the Temporomandibular Joint of the Mouse Measured by MR Imaging at 7T

Abstract: Purpose: We analyzed the anatomical structure of the temporomandibular joint (TMJ) and molecular weight dependency of synovial membrane permeability in mice using 7-tesla magnetic resonance (MR) imaging.Methods: We obtained 3-dimensional (3D) T 1 -weighted gradient echo (3D-T 1 W) and 3D T 2 -weighted rapid acquisition with relaxation enhancement (3D-T 2 W RARE) MR images of the TMJ of male C57BL6 mice with voxel resolution of 65 µm. Two-dimensional (2D) T 1 w images were measured every 45 s before and after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…In a previous report, the articular disc of rodent TMJs were depicted using contrast-enhanced MRI [8,9]. In the present study, the articular disc was also observed without contrast reagent and depicted with the reagent in P20 rats (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In a previous report, the articular disc of rodent TMJs were depicted using contrast-enhanced MRI [8,9]. In the present study, the articular disc was also observed without contrast reagent and depicted with the reagent in P20 rats (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Gd-DTPA (200 nM Gd/ g body weight) was used for the dynamic study. MR images of the TMJ were obtained with a 7-tesla microimaging system (AVANCE III, Bruker Biospin, Ettlingen, Germany) with ParaVison operating software (version 5.1, Bruker Biospin), as previously described [8,9]. The coronal plane image was defined as a slice vertical to the base of the brain and vertical to the midline.…”
Section: Magnetic Resonance Microimaging Of the Rat Tmjmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed tomography (CT) and magnetic resonance (MR) imaging are used in clinical practice and are often applied to determine the treatment strategies and evaluate their effects. There are only few studies which have radiologically evaluated the results of histopathological findings using animal disease models (4,5). Thus, the relationship between actual pathological changes and radiological findings therefore remains unclear.…”
mentioning
confidence: 99%